2004
DOI: 10.1002/uog.1105
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neurological damage in monochorionic twins with selective intrauterine growth restriction and intermittent absent or reversed end‐diastolic umbilical artery flow

Abstract: K E Y W O R D S:intermittent absent or reversed end-diastolic flow; intrauterine fetal death; leukomalacia; monochorionic twins; neurological damage; selective intrauterine growth restriction (overall 9/44 (20.5%) vs. 0/40, P < 0.001; smaller twin 6/22 (27.3%) vs. 0/20, P < 0.05) and parenchymal brain damage (overall 7/35 (20.0%) ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
142
1
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 19 publications
7
142
1
14
Order By: Relevance
“…An important factor, which may strongly influence the rate of cerebral injury, is gestational age at delivery. In the cohort from Gratacos et al, mean gestational age at delivery was lower (30.7 weeks' gestation) (Gratacos et al, 2004) than in our cohort and in the study from Chang et al (33.2 and 33.4 weeks' gestation, respectively) (Chang et al, 2010). Lower gestational age rather than sIUGR or Doppler flow patterns may account for the discrepancy in results between the studies.…”
Section: Discussioncontrasting
confidence: 76%
“…An important factor, which may strongly influence the rate of cerebral injury, is gestational age at delivery. In the cohort from Gratacos et al, mean gestational age at delivery was lower (30.7 weeks' gestation) (Gratacos et al, 2004) than in our cohort and in the study from Chang et al (33.2 and 33.4 weeks' gestation, respectively) (Chang et al, 2010). Lower gestational age rather than sIUGR or Doppler flow patterns may account for the discrepancy in results between the studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Selective intra-uterine growth restriction (sIUGR) and twin-to-twin transfusion syndrome (TTTS) complicate monochorionic (MC) twin pregnancies, and are associated with a high risk of intra-uterine demise and neurological adverse outcome (Adegbite et al, 2004(Adegbite et al, , 2005Gratacos et al, 2004;Sebire et al, 1997;Victoria et al, 2001). Natural history of sIUGR in MC twin pregnancies is different to that in dichorionic (DC) twins and singletons because of the presence of placental anastomoses (Denbow et al, 2000).…”
mentioning
confidence: 99%
“…Doppler flow velocimetry has been found a good method in examining the status and path of blood flow in fetal circulation [18] D. Previously, color Doppler ultrasonography has been used with success in examining the fetal circulation in terms of pathologic conditions such as intrauterine growth abnormalities, fetal anemia, and twin-to-twin transfusion syndrome [19][20][21][22]. However, its use, as a modality to determine the prognosis of twin or multiple pregnancies on the basis of chorionicity has been rarely studies [23,24]. For example, in a study by Fichera et al [25], the sensitivity and specificity of this method were 75% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Zuckerwise et al [27] also concluded that in monochorionic twin pregnancies with fetal growth retardation, color Doppler ultrasonographic findings might be abnormal. On the other hand, it has been shown that in uncomplicated monochorionic pregnancies before the week 28, color Doppler ultrasonographic findings might be abnormal [28] and single abnormal findings may indicate the presence of certain placental anastomosis and not essentially a hazardous, unfavorable condition [4,10,23]. So, it is important to include abnormal twin pregnancies in terms of neonatal-fetal abnormalities in future studies.…”
Section: Discussionmentioning
confidence: 99%